Sinergismo entre clorexidina e hidróxido de cálcio sobre as propriedades mecânicas da dentina radicular - Ribeiro, Michael R. Garcia (2014)
Objective: To evaluted the synergistic effect of the solution of chlorhexidine 2 % (CHX) as endodontic irrigating and Calcium hidroxyde (HC) folder as osteoinductive material on mechanical properties of root dentin RMF , E and Off-set 2 % after 30 , 90 and 180 days. Methods: 90 bovine incisors were used to make bars dentin (BD's) were randomly divided into 3 groups controls (n= 10 per group) and 2 experimental groups (n= 30 per group) : negative control group (GCN= Distilled and deionized water – [WDD]) ; positive control group 1 (GCp1= NaOCl 2.5%/EDTA 17 %), positive control group 2 (GCp2= 2.0% CHX/ADD), Experimental group 1 (EG1= NaOCl 2.5%/EDTA 17% + HC) and Experimental group 2 (GE2= CHX 2.0%/ADD + HC). The GE 's were divided into 3 groups (n = 10) as the exposure time (T1= 30 , T2= 90 and T3= 180 days). The GC 's were considered baselines (T0). BD 's were tested as flexural strength to obtain the average values of RMF , E and Offset 2 % . The data were subjected to statistical analysis (α= 0.05). Results: In the highest averages of baselines RMF , E and Off-set 2 % were observed in the GCN and GCp2 (P< 0.05) . The RMF in GE2˃GE1 at all times evaluated (P<0.05). For E, GE1=GE2 in T1 and T3, GE2˃GE1 in T0 and T2. To Off-Set 2% GE2˃GE1 in all subgroups except in T2. It has been observed more frequently in BD's vertical fracture T3 for GE1 and GE2 to oblique (P<0.05). Conclusion: The results suggest synergism positive trend solution of CHX 2.0% to HC for preserving the mechanical properties of the tested root canal over time. Clinical Relevance: Within the limitations of this in vitro study may be speculated that , clinically, the CHX 2.0% solution is an agent of preservation of the mechanical properties of root dentin.